Skeletal malformations in Australian marine finfish hatcheries - Cobcroft, JM; Battaglene, SC (Aquaculture, 2013)
The Australian finfish aquaculture industry has a target to more than treble production from 2005 to100,000 t p.a. by 2015. Most of the current production is from sea cage culture of Salmo salar and Thunnusmaccoyii but new and emerging species are predicted to have a faster increase in production and were thefocus of this study. The quantity and quality of hatchery-produced fingerlings is an impediment to achievinggrowth in the marine finfish sector. A survey of 18 hatcheries revealed that 44% indicated skeletalmalformations were a significant issue in hatchery production, and 89% reported variability in malformationrates between production batches. Samples of fish from selected hatcheries were cleared and stained forassessment of abnormal bone development. Two hatcheries that had indicated malformations were not asignificant problem submitted samples with >5% severe malformations. Jaw and spinal malformationsoccurred in Lates calcarifer, Seriola lalandi, Epinephelus fuscoguttatus, E. coioides, and Latris lineata. To thebest of our knowledge, causative factors of malformations in Australian hatcheries have only been identifiedfor jaw malformation in Lates calcarifer and Latris lineata, and further research is either needed or underwaywith other species and malformation types in order to improve culture protocols and increase fingerlingquality. Improved monitoring techniques for skeletal malformations would substantially enhance the comparisonof production methods at a commercial scale and enhance research efforts.